PERAN KEPALA SEKOLAH DALAM MENGEMBANGKAN PRESTASI NON-AKADEMIK SISWA DENGAN GANGGUAN PENDENGARAN DI SEKOLAH LUAR BIASA - M. Khairul Lutfi; M. Irfandi; Abdul Khair; Nindya Seva Kusmaningsih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the role of the principal in the form of (Manager, Administrator, Supervisor, and Collaborator), as well as the obstacles faced in developing non-academic achievements of students with hearing impairments in Special Schools. This study uses a qualitative research method with a case study type. The subject of this study is the principal at one of the special schools in Yogyakarta. Data collection uses interview, observation, and documentation techniques with the researcher as the main instrument. The data analysis method used is Milles, Huberman, and Saldana, which includes the process of data collection, data reduction, data presentation, and drawing conclusions. Data validity is used data triangulation, and member checking. The results of the study show that the role of the principal is shown in several categories, namely Manager, namely by developing non-academic achievements that are adjusted to the Vision, Mission, and school curriculum, as well as coaching achievements that are adjusted to students' talents and interests. Administrator, carried out in the form of the principal providing supporting resources such as BOS funds, coaches, and providing complete facilities and infrastructure to support students' talents and interests. Supervisors, which are carried out in the form of coaching and supervision to all related parties, starting from educators, parents, using a collaborative approach, and taking an intensive approach to parents to encourage parents' contributions to their students' non-academic achievements. Collaborators, this activity is carried out by building collaboration with all parties both internal and external to the school, as well as related institutions by building cooperation between schools or higher education institutions and the government. The principals face in carrying out the process of coaching non-academic achievements, namely (1) the principal experiences difficulty in unifying perceptions, (2) miscommunication occurs between related stakeholders, and (3) the principal experiences difficulty in finding competent coaches who will become coaches in developing the non-academic achievements of students with special needs.